2022
DOI: 10.3390/jcm11102686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manual Therapy Compared to Ibuprofen on Primary Dysmenorrhea in Young Women—Concentration Assessment of C-Reactive Protein, Vascular Endothelial Growth Factor, Prostaglandins and Sex Hormones

Abstract: Background: The study aimed to assess if manual therapy, compared to ibuprofen, impacts the concentration of inflammatory factors, sex hormones, and dysmenorrhea in young women Methods: Thirty-five women, clinically diagnosed with dysmenorrhea, were included in the study. They were divided into group A—manual therapy (n = 20) and group B—ibuprofen therapy (n = 15). Inflammatory factors such as vascular endothelial growth factor (VEGF), C-reactive protein (CRP), prostaglandin F2α (PGF2α), E2 (PGE2) and sex horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Herein, athletes were randomised into three even groups (1:1:1) via an urn (adaptive biased coin) design, using printed cards in closed envelopes indicating group allocation [ 37 , 38 , 39 ]. The intervention group (IG) received a standardised IAMT.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, athletes were randomised into three even groups (1:1:1) via an urn (adaptive biased coin) design, using printed cards in closed envelopes indicating group allocation [ 37 , 38 , 39 ]. The intervention group (IG) received a standardised IAMT.…”
Section: Methodsmentioning
confidence: 99%
“…But clinical studies have shown a physiological rationale for dysmenorrhea that is directly linked to elevated levels of endometrial and menstrual fluid prostaglandins (PGs). The first two days of menstruation are when PG levels are at their peak, causing significant abdominal pain and discomfort that extends to the lower back and thighs and interferes with everyday activities [7].…”
Section: Discussionmentioning
confidence: 99%
“…2 12 The side effects of these drugs and the nature of the periodic recurrence of menstrual cramps indicate that women are more willing to seek non-pharmacological methods to manage PD. 13 Currently, a range of non-drug interventions are available for the treatment of PD, including acupuncture (e.g., manual acupuncture, electroacupuncture, auriculotherapy) 14 ; transcutaneous electrical nerve stimulation 15 ; acupressure 16 ; aromatherapy 17 ; physical activities (e.g., aerobic exercise, resistance training, balance training, stretching) 18 ; physiotherapy (e.g., thermotherapy, electrotherapy, kinesio tape) 19 ; psychological intervention (e.g., biofeedback, relaxation, hypnotherapy, imagery) 20 ; nutritional and dietary supplements (e.g., vitamin, fennel, zinc, ginger) 21 ; and manual therapy (e.g., massage, tuina, manipulation techniques) 22 . Clinical practice guidelines have recommended some of these non-pharmacological interventions for pain relief in PD, 23 and systematic reviews based on randomized controlled trials (RCTs) have also confirmed that several non-drug therapies can effectively relieve menstrual pain and improve the quality of life (QoL) and emotional well-being in women with PD.…”
Section: Introductionmentioning
confidence: 99%